Co‐sensitized cells from Antarctic resources using Ag nanoparticles. (5th July 2020) - Cerdá, María Fernanda; Botasini, Santiago
Abstract : In the present work, we explore in photoanodes of dye‐sensitized solar cell (DSSC) the co‐sensitization of the red protein phycoerythrin extracted from Antarctic algae with spherical silver nanoparticles between 10 and 200 nm and triangular nanoparticles of 100 nm. We found that the order of addition of the sensitizers matters. Best results achieved for a sequential approach was phycoerythrin used as a dipping solution at the first step and nanoparticles at the second. We found that cell efficiency depends on the protein concentration, although no main differences detected with the nanoparticle shape or size. Our results show an average increase of 25% in the conversion efficiency values in the presence of nanoparticles.